Can Sound Health Insurance Increase the Internal Circulation in the Economy of China? - Zhao, Peng; Wang, Li-Yong; Zhao, Li (Frontiers in Public Health, 2021)
In 2020, President Xi Jinping put forward a constructing cycle, that has been given priority in this paper. This particular cycle, when considered within the inner loop and outer loop, promotes the guiding ideology of the new development pattern of the binary economy that exists today. Therefore, in order to gauge the extent of the promotion of domestic production and consumption, from the perspectives of medical expenses, this paper refers to the bootstrap rolling window causality method, which considers the evidence-based medical spending on the consumption Granger causality. The results show that the Granger causality exists between medical expenditure and consumption expenditure, at different time interval endpoints. In contrast, however, the variable of consumption does not produce Granger causality between medical expenditure and consumption. In this regard, a series of measures, such as increasing medical insurance expenditure, improvement of the medical insurance system, reduction of the housing price rise, and increasing government investment, have been proposed, so as to promote the development of the domestic circular economy.